2012
DOI: 10.4081/reumatismo.2012.158
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cyclic intravenous iloprost in systemic sclerosis: clinical experience from a single center

Abstract: The aim of the present study was to retrospectively evaluate response to therapy in 73 patients affected by systemic sclerosis (SSc) who underwent long-term cyclic treatment with intravenous iloprost for peripheral vascular involvement (average duration of treatment 54.12±41.04 months). Seventy-three SSc patients were enrolled. Data were collected by reviewing clinical records and by phone or direct interview. Patients underwent a thorough physical examination at the end of follow up. The incidence of severe v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Most patients on monthly iloprost infusions experience complete clinical resolution in the first year of treatment with the 10-year survival rate reaching in one cohort 55.6% [ 13 ]. In the absence of tools such as capillaroscopy, which require a certain level of experience and are operator dependent, simple clinical tests such as Allen’s test that can be performed easily at bedside can be employed as predictors of patient outcome; DUs in patients with a negative Allen’s test show expedited healing times [ 14 ]. Clinical improvement and a switch to easier, more cost-efficient ways of administration such as an elastomeric pump seem to be the main reasons of drug discontinuation [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients on monthly iloprost infusions experience complete clinical resolution in the first year of treatment with the 10-year survival rate reaching in one cohort 55.6% [ 13 ]. In the absence of tools such as capillaroscopy, which require a certain level of experience and are operator dependent, simple clinical tests such as Allen’s test that can be performed easily at bedside can be employed as predictors of patient outcome; DUs in patients with a negative Allen’s test show expedited healing times [ 14 ]. Clinical improvement and a switch to easier, more cost-efficient ways of administration such as an elastomeric pump seem to be the main reasons of drug discontinuation [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…No severe side effects reported. Martins et al/2022 [ 13 ] Observational retrospective study dSSc:9, lSSc: 37 60 N/A 44 Monthly infusion at 0.5–1.5 ng/kg /min, infusion rate as tolerated starting at 4 mL/h and increased by increments of 4 up to 16 mL/h 86.4% of patients: DUs healing in the first 6 months Safety: generalised erythroderma in one patient, others with minor AEs, 5-year survival rate: 68.2% Casigliani et al/2012 [ 14 ] Observational retrospective study dSSc: 31, lSSc: 42 73 N/A 28 Monthly infusion at 0.5–1.5 ng/kg /min, infusion rate as tolerated Complete healing in 89.4% of the patients after the first treatment Jamart/2022 [ 16 ] Observational longitudinal retrospective study dSSc:10, lSSc: 31 41 D2 13 Iloprost Infusion > 5 days vs. < 5 days Median infusion rate of 1.7 ng/kg/min. Number of patients with complete DU healing at day 90 was significantly higher among patients who received > 5 days of iloprost: 51 vs. 37% ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, NVC is applicable to follow the effects of treatments used in SSc. However, there are currently only a few pilot studies (nonrandomized, nondouble-blind, and nonplacebo-controlled) on this topic [15,[61][62][63][64][65][66][67][68][69].…”
Section: The Nvc In Systemic Sclerosis: Clinical Applicationmentioning
confidence: 99%
“…23 Unfortunately, iloprost and other prostanoids have a short half-life and pharmacological effect, 24 and cyclical repetitions of therapy are needed. 25 On the basis of these results, European League Against Rheumatism (EULAR) guidelines state that iloprost IV (0.5-2 ng/kg/min 6-8 hours per day for 3-5 consecutive days) should be considered in the treatment of DUs in SSc patients (strength of recommendation: A). 26 Regarding dosage, there is evidence that low-dose (0.5 ng/kg/min) and high-dose (2 ng/kg/min) iloprost have substantially the same effectiveness in long-term treatment.…”
Section: Prostanoidsmentioning
confidence: 99%
“…27 Multiple studies have shown that administration of a mean iloprost dose of 1 ng/kg/min results in well-tolerated therapy without losing clinical efficacy. 8,23,[25][26][27] As the results of the medical literature are not homogeneous, iloprost administration dose has to be tailored in accordance with the patient's individual tolerability.…”
Section: Prostanoidsmentioning
confidence: 99%